Husband's migration status and contraceptive behaviors of women: evidence from Middle-Ganga Plain of India - Ramkrishna Samanta; Jadab Munda (BMC, 2023)
Abstract Background Male out-migration is negatively associated with contraceptive use in developing countries. This study aimed to examine the effect of male out-migration on the contraceptive behaviour of women in the Middle-Ganga Plain (MGP) region. Methods The data has been collected from the Middle-Ganga Plain survey (2018-19), which was conducted by the International Institute for Population Sciences (IIPS). The overall sample size was 1314 wives left behind and 1402 non-migrant wives. Multivariate logistic regression analysis was used to examine the relationship between the variables. Statistical analyses were done using SPSS version 25. Result The result shows that female sterilization was the most common method used by both left behind wives (30.9%) and non-migrant wives (34.6%). Most of the left-behind women didn't use contraception because their husbands were away from home (30.86%). The result also shows that left behind wives were less likely to use any methods of contraception than the non-migrant wives. Left behind women were more tended to use the modern methods (OR-0.71, 95%CI = 0.57-0.88) than any traditional methods (OR-0.61, 95% CI = 0.46-0.80). Age, religion, family type, working status, and marital duration were strongly associated with women's contraceptive use. Conclusion These results strengthen the existing literature that explains how migration affects women's health. Therefore, there is an important need to develop and implement comprehensive education programs and policy on contraception use.